2000
DOI: 10.1038/sj.onc.1203935
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus-mediated p16INK4a gene expression radiosensitizes non-small cell lung cancer cells in a p53-dependent manner

Abstract: We examined the in¯uence of adenovirus-mediated wildtype p16 INK4a (Ad/p16) expression on the radiation sensitivity of NSCLC cell lines, all of which lacked constitutive p16 INK4a but each of which varied in p53 status: A549 (7p16 INK4a /+pRb/wt-p53), H322 (7p16 INK4a /+pRb/mt-p53), and H1299 (7p16 INK4a / +pRb/deleted-p53). The in vitro clonogenic survival results indicate that Ad/p16 enhanced the radiosensitivity of A549 but not H322 or H1299. Further analysis indicated that the apoptosis induced by combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
27
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 21 publications
2
27
0
Order By: Relevance
“…We found that Adv/p16 infection induced cleavage of MDM2 and upregulation of p53 prior to triggering apoptosis. Others have shown that accumulation of the p53 protein by Adv/p16 sensitizes NSCLC to irradiation (Kawabe et al, 2000). These observations support the possibility that caspase-3 activation-induced cleavage of MDM2 results in transient p53 activation, leading to induction of apoptosis in Adv/p16-infected A549 cells; direct interactions among these molecules, however, should be further examined.…”
supporting
confidence: 45%
“…We found that Adv/p16 infection induced cleavage of MDM2 and upregulation of p53 prior to triggering apoptosis. Others have shown that accumulation of the p53 protein by Adv/p16 sensitizes NSCLC to irradiation (Kawabe et al, 2000). These observations support the possibility that caspase-3 activation-induced cleavage of MDM2 results in transient p53 activation, leading to induction of apoptosis in Adv/p16-infected A549 cells; direct interactions among these molecules, however, should be further examined.…”
supporting
confidence: 45%
“…The results indicate that the cell survival of these cancer cell lines was substantially decreased by Ax-hp16 infection (data not shown) (Kawabe et al, 2000;Yokozaki, 2000). These findings suggest that adenovirus-mediated p16 gene transfer increased radiosensitivity via nonapoptotic cell killing in these other human cancer cell lines.…”
Section: Discussionmentioning
confidence: 82%
“…Previous findings indicate that p16-dependent downmodulation of pRb levels in the presence of overexpressed wild-type p53 causes apoptosis only in tumour cells, whereas normal cells arrest in G1 (Sandig et al, 1997). Kawabe et al (2000) U251MG cells Figure 4 Effect of p16 or p21 transduction with or without irradiation on nuclear morphologic changes. U251MG or D54MG cells were treated as described in the TUNEL assay, and nuclear morphologic changes in these treated cells were evaluated using Giemsa staining 7 days after irradiation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations